Experiment on critical heat flux of subcooled flow boiling in compound heat transfer tubes. (25th November 2021) - Liu, P.; Guo, Y.S.; Zheng, W.L.; Song, Y.T.; Peng, X.B.; Tang, M.Y.; Wang, W.H.; Huang, S.F.; Ji, J.D.; Chen, Q.H.; Mao, X.
Highlights: The DNB-type CHF characteristics of subcooled flow boiling in compound heat transfer tubes have been investigated. The combination of twisted tape inserts and internal thread can delay the occurrence of CHF. The CHF was directly proportional to the pitch, mass flux and pressure and inversely proportional to the twist ratio. Abstract: In order to enhance the Departure from Nucleate Boiling (DNB) type critical heat flux (CHF) of the divertor in International Thermonuclear Experimental Reactor (ITER), the novel compound heat transfer tube (CHTT) was proposed as a compound CHF enhancement technique by inserting a twisted tape into an internal thread tube (ITT). Firstly, the experiments were investigated for subcooled water flow boiling on four kinds of cooling tubes, including plain tube (PT), tube with twisted tape inserts (TWTT), ITT and CHTT, covering system pressures from 0.2 to 0.8 MPa, inlet temperatures from 25 to 65 ℃, mass fluxes from 543 to 2935 kg/m 2 s and heat fluxes from 1 to 17 MW/m 2 . The experimental results showed that the CHTT combined by using the twisted tape inserts and internal thread tube performed better in enhancing the subcooled CHF than the individual technique. The values of CHF in CHTT could be improved by 33.19%, 55.14% and 130.71%, respectively, compared with that of the TWTT, ITT and PT, respectively. Secondly, the effect of twist ratio, pitch, mass flux and pressure on CHF were also analyzed in CHTT. The CHF was directly proportional to the pitch, mass flux and pressure and inversely proportional to the twist ratio. Finally, the five existing subcooled CHF correlations were evaluated based on the present experimental data in CHTT. It was found that the Tong-75-Ⅱ correlation showed the best prediction accuracy with a mean absolute error (MAE) of 32.80% and a root mean square error (RMSE) of 33.72%.